Pengaruh Ketebalan Bulu Ayam dalam Kotak Kayu sebagai Peredam Suara untuk Menurunkan Intensitas Kebisingan Mesin Penggiling Daging di Pasar Serangan Yogyakarta - Siska Septiana; Adib Suyanto; Sri Muryani (Poltekkes Kemenkes Yogyakarta, 2013)
The use of meat grinding machine produce sound with high noise intensity which can be harmful for the health and safety of workers operating the machine. Based on a preliminary survey con-ducted in 5 February 2013 at a meat shop belongs to Mr “X” located in Serangan Market of Yogyakarta, it was known that the noise intensity yielded from the grinding machine was record-ed as high as 100.4 to dB (A). Hence, this condition needs efforts to reduce the noise in order to prevent health effects which can be caused by long term and execessive exposure. One method that can be applied is by utilizing chicken feathers waste as noise reducer, and this study was aimed to determine the influence of thickness variation of the feather by doing an experiment with pre-test post-test control design. The wooden box muffler containing chicken feathers and covered the machine was made from sengon wood and laminated by plywood. The noise mea-surement were carried out in six replications for each feathers thickness by using sound level meter following the standard measurement and calculation. The results of the study showed that the feather thickness variation of 10 cm, 20 cm and 30 cm, were corresponded with in average of 14,9 %, 16,0 % and 17,5 % noise reduction, respectively. Analysis by using one way anova sta-tistical test at 95 % level of signifcance, found that the differences among the amount of the reduction were significant, and therefore it can be concluded that feather can reduce the machin-al noise level. Subsequent LSD test found that the 30 cm thickness was the most effective.